MULTISENSORY APPROACH IN TRADITIONAL DANCE LEARNING FOR STUDENTS WITH SPECIAL NEEDS IN INCLUSIVE ELEMENTARY SCHOOL CLASSROOMS: A SYSTEMATIC LITERATURE REVIEW - Yulia Anggraeni; Ai Sutini (RADJA PUBLIKA, 2025)
This study aims to systematically review the implementation of multisensory approaches in traditional dance learning for students with special needs in inclusive elementary school classrooms. The method used is a systematic literature review following the PRISMA 2020 guidelines. Literature searches were conducted in Google Scholar, ERIC, and accredited national journal portals with a publication range of 2018-2024. Of the 156 identified articles, 24 articles met the inclusion criteria for analysis. The review results indicate that multisensory approaches integrating visual, auditory, kinesthetic, and tactile modalities have proven effective in enhancing participation and learning achievement in traditional dance for students with special needs. The most commonly used strategies include visual aids, music with clear rhythms, modified movements, and the use of textured dance properties. The main challenges faced by teachers include limited training, minimal resources, and lack of specific curriculum guidelines. This study recommends the development of multisensory-based traditional dance learning modules and enhancement of teacher capacity in managing inclusive classrooms.